1997
DOI: 10.1177/096120339700600510
|View full text |Cite
|
Sign up to set email alerts
|

Risk for venous thrombosis related to antiphospholipid antibodies in systemic lupus erythematosus—A meta-analysis

Abstract: Patients with SLE and LA are at approximately six times greater risk for VT than patients without LA, whereas patients with SLE and aCL are approximately two times greater risk for VT than patients without aCL. We have identified important methodologic limitations and differences in study characteristics. Other risk factors for VT have not been thoroughly evaluated in these studies. Further studies are needed that provide an accurate estimate of the absolute risk for aPL related VT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
2
8

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 261 publications
(131 citation statements)
references
References 22 publications
7
114
2
8
Order By: Relevance
“…For the first time, we believe, EMPs are in evidence in normal human plasma and are found to be increased in patients selected according to a biological abnormality, namely being positive for LA. This coagulation abnormality is well recognized to be strongly associated with a thrombotic tendency (31,32). This association has been termed antiphospholipid syndrome (APS).…”
Section: Figurementioning
confidence: 99%
“…For the first time, we believe, EMPs are in evidence in normal human plasma and are found to be increased in patients selected according to a biological abnormality, namely being positive for LA. This coagulation abnormality is well recognized to be strongly associated with a thrombotic tendency (31,32). This association has been termed antiphospholipid syndrome (APS).…”
Section: Figurementioning
confidence: 99%
“…Any information about authors, journals, and institutions was deleted for the purpose of quality assessment. The scoring system was adapted from the meta-analyses by Wahl et al 5,6 The quality assessment form encompassed 64 items distributed in 4 categories: clinical criteria (SLE patients classified or not according to the American College of Rheumatology classification 15,16 and measure of disease activity); echocardiographic diagnosis of the outcome (HVD) 7 ; definition of the exposure to aPL 7,[17][18][19][20] ; and statistical analysis and control for confounders. Finally, a score was obtained for each category for all studies.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…A ntiphospholipid antibodies (aPL) may be considered either as risk factors for arterial or venous thrombosis as well as recurrent fetal losses [1][2][3][4][5][6] or as markers of the so-called antiphospholipid syndrome (APS). APS is characterized by venous or arterial thromboses and obstetric morbidity associated with persistent aPL according to the classification criteria.…”
mentioning
confidence: 99%
“…The association of venous thrombosis with antiphospholipid antibodies (aPL) (IgG and IgM anticardiolipin antibodies and lupus anticoagulant [LAC]) has been well established; this has been observed in patients without an underlying autoimmune disease (3), but has particularly been found in patients with SLE (4). The association has been primarily identified in retrospective studies; more recently, a systematic review, a meta-analysis, and a prospective study have confirmed this association (2,4,5).…”
mentioning
confidence: 99%